Drug‐induced linear immunoglobulin A bullous dermatosis: A French retrospective pharmacovigilance study of 69 cases. Issue 3 (4th January 2019) - Garel, Bethsabée; Ingen‐Housz‐Oro, Saskia; Afriat, Daniele; Prost‐Squarcioni, Catherine; Tétart, Florence; Bensaid, Benoit; Bara Passot, Corina; Beylot‐Barry, Marie; Descamps, Vincent; Duvert‐Lehembre, Sophie; Grootenboer‐Mignot, Sabine; Jeudy, Géraldine; et al.
Abstract : Aims: Linear immunoglobin A (IgA) bullous dermatosis is a rare autoimmune dermatosis considered spontaneous or drug‐induced (DILAD). We assessed all DILAD cases, determined the imputability score of drugs and highlighted suspected drugs. Methods: Data for patients with DILAD were collected retrospectively from the French Pharmacovigilance network (from 1985 to 2017) and from physicians involved in the Bullous Diseases French Study Group and the French Investigators for Skin Adverse Reactions to Drugs. Drug causality was systematically determined by the French imputability method. Results: Of the 69 patients, 42% had mucous membrane involvement, 20% lesions mimicking toxic epidermal necrolysis (TEN), 21% eosinophil infiltrates and 10% keratinocytes necrosis. Direct immunofluorescence, in 80%, showed isolated linear IgA deposits. Vancomycin (VCM) was suspected in 39 cases (57%), 11 had TEN‐like lesions, as compared with three without VCM suspected. Among the 33 patients with a single suspected drug, 85% had an intrinsic imputability score of I4. Among them, enoxaparin, minocycline and vibramycin were previously unpublished. For all patients, the suspect drug was withdrawn; 15 did not receive any treatment. First‐line therapy for 31 patients was topical steroids. Among the 60 patients with available follow‐up, 52 achieved remission, 10 without treatment. Four patients experienced relapse, four died and five had positive accidental rechallenges. Conclusions: There is no major clinical difference between DILAD and idiopathic linear IgA bullous dermatosis, but the former features a higher prevalence of patients mimicking TEN. VCM, suspected in more than half of the cases, might be responsible for more severe clinical presentations. We report three new putative drugs.